VD_FINDINFO HC / 2023 / 570 vom 17. Juli 2023 - VD Tribunal cantonal (2023)
ASSISTANCE JUDICIAIRE, RÉVOCATIONEN GÉNÉRAL, DÉNUEMENT, EX TUNC, RÉTROACTIVITÉ | 117 CPC (CH), 117 let. a CPC (CH), 120 CPC (CH), 121 CPC (CH)